Dietary diversity and possible sarcopenia among older people in China: a nationwide population-based study - Du, Qiaoqiao; Lu, Yanhui; Hu, Fan; Feng, Xinglin; Zhang, Yunquan; Li, Shaojie; Zhang, Chi; Zhang, Hua; Zeng, Yi; Yao, Yao; Lu, Zhaohui; Zhang, Wenya; et al. (Frontiers in Nutrition, 2023)
Background Sarcopenia is a common geriatric disease. Many dietary factors may contribute to the development of sarcopenia. Few studies have been conducted on dietary diversity and sarcopenia in Chinese older adults. Among a nationwide sample, the objective of this study is to assess the association between the dietary diversity score (DDS) and the prevalence of possible sarcopenia. We considered the different patterns of dietary diversity in relation to possible sarcopenia. Methods We conducted this analysis utilizing the cross-sectional data from the 2012, 2014, and 2018 waves of the Chinese longitudinal healthy longevity survey (CLHLS). A standard developed by the Asian Working Group for Sarcopenia 2019 (AWGS2019) was used to assess the possibility of sarcopenia. On the basis of the DDS generated by previous studies, we have constructed four new indicators as follows: total diet, animal-based diet, plant-based diet, and plant-based diet without the consumption of legume products and nuts. We used the generalized estimation equation (GEE) model to evaluate the associations between the DDS of the total diet, animal-based diet, plant-based diet, and plant-based diet without the intake of legume products and nuts and possible sarcopenia. These associations were statistically adjusted for a variety of potential confounders. Sensitivity analysis was performed by excluding some participants who were long-term bedridden, had Alzheimer's disease, or were terminally ill. Results The analysis included 6,624 participants (mean age 83.4 years at baseline). In our study, we found that participants with a higher DDS of the total diet (OR = 0.62; 95% CI: 0.51–0.77), animal-based diet (OR = 0.62; 95% CI: 0.49–0.79), and plant-based diet (OR = 0.64;95% CI: 0.51–0.80) were at a lower risk of developing sarcopenia. In sensitivity analyses, the associations remained unchanged. Conclusion Taking a diversified diet, including animal foods, may reduce the risk of developing sarcopenia. According to the findings of this study, adopting a diversified diet might reduce the risk of sarcopenia for older adults.